Circulating haematopoietic progenitors during treatment of renal anaemia with recombinant human erythropoietin - Göbel, Verena; Hoffmann, Hans-Georg; Müller-Wiefel, Dirk E.; Braun, Andrea; Ludwig, Rolf; Schärer, Karl; Debatin, Klaus-Michael (European journal of pediatrics, 1994)
The effect of recombinant human erythropoietin (rhEPO) and interleukin 3 (IL3) on circulating haematopoietic progenitors consisting mainly of immature burst-forming-units-erythrocytes (BFU-E), was investigated in ten paediatric patients treated by regular haemodialysis. During a 30-week study rhEPO treatment resulted in a rise of median haemoglobin levels from 6.7 g/dl to >10 g/dl in all patients. Before initiating rhEPO treatment the number of circulating BFU-E in chronic renal failure patients responded to grading doses of rhEPO in vitro similar to that in control children; however, the dose-response curves were not predictive for the in vivo response to rhEPO. After an initial rise in five patients BFU-E numbers declined by week 30 of rhEPO treatment. BFU-E numbers decreased to 35% of pretreatment values. The number of granulocyte-macrophage colony forming cells (GM-CFC) also decreased during rhEPO treatment. Addition of IL3 to the culture medium containing saturating concentrations of granulocyte-macrophage colony stimulating factor did not stimulate BFU-E numbers of patients before rhEPO treatment or those of controls. However, 2 weeks after start of rhEPO treatment IL3 increased the growth of patient's BFU-E in vitro to 220% of pretreatment levels, followed by a gradual decrease of stimulation until the end of observation. These findings indicate that: (1) long-term recruitment of circulating haematopoietic progenitors during rhEPO treatment is low in children with renal anaemia; (2) rhEPO sensitivity of circulating BFU-E is not predictive for the in vivo response; (3) rhEPO treatment results in enhanced sensitivity of BFU-E to IL3.
Gesehen am 24.09.2024